2019
DOI: 10.1371/journal.pone.0222082
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of loss to follow-up among HIV-infected children in an antiretroviral treatment program

Abstract: IntroductionThe success of antiretroviral treatment (ART) programs can be compromised by high rates of patient loss to follow-up (LTFU). We assessed the incidence and risk factors of LTFU in a large cohort of HIV-infected children receiving ART in Thailand.MethodsAll children participating in a multicenter cohort (NCT00433030) between 1999 and 2014 were included. The date of LTFU was 9 months after the last contact date. ART interruption was defined as ART discontinuation for more than 7 days followed by resum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…For example, a study conducted in India on the same population reported that age affected treatment outcomes such as LTFU [ 73 ], as did cohort data from the Asia-Pacific region, the Caribbean, and Central and South America [ 25 ]. However, at least one study conducted in Thailand [ 26 ] reported that LTFU was higher among younger ALHIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study conducted in India on the same population reported that age affected treatment outcomes such as LTFU [ 73 ], as did cohort data from the Asia-Pacific region, the Caribbean, and Central and South America [ 25 ]. However, at least one study conducted in Thailand [ 26 ] reported that LTFU was higher among younger ALHIV.…”
Section: Discussionmentioning
confidence: 99%
“…Cohort data from the Asia-Pacific, the Caribbean, and Central and South American regions [ 25 ] have found LTFU associated with gender, age, and rural settings. Data from Thailand [ 26 ] have indicated that age and malnutrition have a significant association with LTFU.…”
Section: Introductionmentioning
confidence: 99%
“…Although, one study revealed people who were initiating ART at an older age were more likely to discontinue their treatment [34]. Also, according to some studies, adolescents and young adults were at higher risk of LTFU compared to both younger children under 10 and adults older than 45 [83]. In children and adolescents, growth retardation due to ART has been cited as one of the important reasons for discontinuation of treatment [83].…”
Section: Discussionmentioning
confidence: 99%
“…Also, according to some studies, adolescents and young adults were at higher risk of LTFU compared to both younger children under 10 and adults older than 45 [83]. In children and adolescents, growth retardation due to ART has been cited as one of the important reasons for discontinuation of treatment [83]. In one study in children under two years of age, the child's nutritional status and side effects of starting treatment, such as diarrhea, were cited as potential reasons for treatment discontinuation [42].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors influencing retention to treatment among CLHIV have been studied including but not limited to age ( 1 , 2 , 18 ), disease stage ( 1 , 19 ), nutritional status ( 18 , 20 ), and history of interrupted ART ( 21 ). However, most of these studies have been facility-based, lacking evidence of the role of community-based programs to support retention in HIV care and treatment services for PLHIV.…”
Section: Introductionmentioning
confidence: 99%